Betting on Diversity – Occupational Segregation and Gender Stereotypes - Urs Fischbacher; Dorothea Kübler; Robert Stüber (Center for Economic Studies and ifo Institute (CESifo), 2022)
Many occupations and industries are highly segregated with respect to gender. This segregation could be due to perceived job-specific productivity differences between men and women. It could also result from the belief that single-gender teams perform better. We investigate the two explanations in a lab experiment with students and in an online experiment with personnel managers. The subjects bet on the productivity of teams of different gender compositions in tasks that differ with respect to gender stereotypes. We obtain similar results in both samples. Women are picked more often for the stereotypically female task and men more often for the stereotypically male task. Subjects do not believe that homogeneous teams perform better but bet more on diverse teams, especially in the task with complementarities. Elicited expectations about the bets of others reveal that subjects expect the effect of the gender stereotypes of tasks but underestimate others' bets on diversity.
Keywords: C91; D90; J16; 330; gender segregation; hiring decisions; teams; discrimination; stereotypes